Developing science monopoly on the force learning material for elementary school students - Ika Maryani; Zia Sumiar (Jurnal Prima Edukasia, 2018)
Natural science learning in elementary schools is considered difficult by students due to its complexity. Teachers have not been fully able to present the natural science lesson in accordance to the characteristics of elementary school students who are still love to play. Those making the learning process and outcomes have not been maximized and require learning media to overcome the problem. This study aimed to: (1) understanding the way to develop science monopoly in Force learning material; and (2) understanding the quality and feasibility of science monopoly. This study was research and development by ADDIE model in five stages, which are; analysis, design, development, implementation, and evaluation. The test of the product was conducted to the 4thgrade students of Muhammadiyah Bausasran 1 Elementary School, Yogyakarta. Instruments have been stated as valid by the expert judgement. The instruments were questionnaire of the feasibility of material, media, and learning expert; questionnaire of students response; and teacher response. Data analysis techniques were qualitative and quantitative data analysis. The assessment score of the media expert validation was 86.5 (very good), subject material expert was 87.5 (very good), learning expert was 85 (very good), teacher response was 100 (very good), and students response was 92.5 (very good).Thus, the learning media of science monopoly on force learning materials for elementary students was already feasible to use as a media of natural science learning.